A Conditional Probit Model for Qualitative Choice: Discrete Decisions Recognizing Interdependence and Heterogeneous Preferences - Hausman, Jerry A.; Wise, David A. (Econometrica, 1978)
Jerry A. Hausman, David A. Wise, A Conditional Probit Model for Qualitative Choice: Discrete Decisions Recognizing Interdependence and Heterogeneous Preferences, Econometrica, Vol. 46, No. 2 (Mar., 1978), pp. 403-426